2021
DOI: 10.3389/fonc.2021.755433
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Cell Death and Immunomodulatory Effects of Cabozantinib

Abstract: Cabozantinib (XL-184) is a multitarget tyrosine kinase inhibitor (TKI) targeting receptor tyrosine kinases (RTKs) involved in oncogenesis and angiogenesis. It is currently the standard therapy for medullary thyroid cancer (MTC), metastatic renal cell carcinoma (mRCC), and hepatocellular carcinoma (HCC). Combination of Cabozantinib with immunotherapy is now a standard treatment in metastatic renal cancer, and its efficacy is being tested in ongoing clinical trial in prostate cancer patients. Here, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
(57 reference statements)
3
19
0
Order By: Relevance
“…Various targets of CZ are associated with immunosuppression, thus allowing it to directly immunomodulate the tumor microenvironment, increase cytotoxic T cell activation/infiltration, and induce susceptibility of tumor cells to cytotoxic T cell-mediated tumor cell killing, differentiating itself from other VEGF-targeting TKIs [ 26 , 37 , 39 , 41 , 43 , 44 , 67 , 74 ]. In particular, TAM kinases such as AXL and MET promote immunosuppressive phenotypes in tumor-associated immunosuppressive cells (including regulatory T cells, myeloid-derived suppressor cells, and tumor-activated macrophages) [ 37 ], which in turn contribute to the resistance against immune checkpoint inhibitors [ 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various targets of CZ are associated with immunosuppression, thus allowing it to directly immunomodulate the tumor microenvironment, increase cytotoxic T cell activation/infiltration, and induce susceptibility of tumor cells to cytotoxic T cell-mediated tumor cell killing, differentiating itself from other VEGF-targeting TKIs [ 26 , 37 , 39 , 41 , 43 , 44 , 67 , 74 ]. In particular, TAM kinases such as AXL and MET promote immunosuppressive phenotypes in tumor-associated immunosuppressive cells (including regulatory T cells, myeloid-derived suppressor cells, and tumor-activated macrophages) [ 37 ], which in turn contribute to the resistance against immune checkpoint inhibitors [ 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, TAM kinases such as AXL and MET promote immunosuppressive phenotypes in tumor-associated immunosuppressive cells (including regulatory T cells, myeloid-derived suppressor cells, and tumor-activated macrophages) [ 37 ], which in turn contribute to the resistance against immune checkpoint inhibitors [ 37 , 41 ]. The combined AXL, VEGFR, and MET inhibition appears to be a relatively unique characteristic of CZ; hence, it is unsurprising that CZ monotherapy promotes unique immunomodulatory effects on innate and adaptive anticancer immunity in advanced RCC [ 26 , 37 , 39 , 41 , 43 , 44 , 67 , 74 ]. Interestingly, CZ-PLGA-NPs treatment significantly promoted the infiltration of cytotoxic CD8 + T cells into the metastatic lung bed ( Figure 8 B), suggesting that CZ-PLGA-NPs may mechanistically support the infiltration of cytotoxic CD8 + T into the tumor microenvironment, enhancing anti-tumor T cell immunity and contributing to the observed reduction in RCC lung metastasis growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, it has become clear that most therapeutic interventions aimed to dampen tumor growth, promote anti-tumor response as a bystander effect by reducing immune suppression and/or enhancing antigen presentation and eliciting T cell responses [ 172 , 173 , 174 ]. This indirect immune modulation contributes to the overall clinical benefit induced by the therapy [ 175 ].…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 In addition, a recent in vitro study showed that cabozantinib triggered immunogenic cell death in prostate cancer cells and directly modulated dendritic cells, suggesting an immunostimulatory role. 22 …”
Section: Introductionmentioning
confidence: 99%